POPULATION STATUS AND HABITAT ASSOCIATION OF SWAYNE’S HARTEBEEST (Alcelaphus Buselaphus Swaynei (Sclater, 1892)) IN MAZE NATIONAL PARK, SOUTHWEST ETHIOPIA - TOLCHA, ABRAHAM; SHIBRU, SIMON; AYECHEW, BELAYNEH (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
We investigated the population status and habitat association of the endemic and emblematic Swayne’s Hartebeest (Alcelaphus buselaphus swaynei) in Maze National Park, Southwest Ethiopia. Line-transect sampling method was used for the population estimation, while habitat association was made based on the abundance of counted individuals in each habitat. Data were analyzed using descriptive statistics and compared with the X2 test. The counted population of Swayne’s Hartebeest in the study period were 1456 and 1492 during wet and dry seasons, respectively showing no seasonal variation. Of these, 31.03% were adult males, 38.53% adult females, 13.95% sub-adult males, 15.96% sub-adult females, and 0.53% young. The number of adult females was higher than in the other age groups followed by adult males in both seasons. Significant differences were observed among age and sex structure during both seasons (wet season: X2= 58.423, df =3, P < 0.05; dry season: X2=534.08, df= 4, P < 0.05). The maximum group size was 36 and the minimum was 1. The ratio of adult males to adult females was 1:1.24 and 1:1.24, sub-adult males to sub-adult females were 1:1.16 and 1:1.12, adult males to sub-adult males was 1:0.36 and 1:0.56, adult females to sub-adult females was 1:0.33 and 1:0.49 in the wet and dry seasons, respectively. The male to female ratio was 1:1.22 and 1:1.19 during wet and dry seasons as well. The population trend among ten years were significantly differed (X2 = 1.71, df= 9, P < 0.05). The Swayne’s Hartebeest was distributed in three habitat types (grassland, riverine forest, and scattered trees) with significant differences (X2=1109.94, df = 3, P < 0.05). The grassland was most preferred by the animal followed by the scattered tree habitat. Managing its habitats is recommended for sustaining the population of the animal